2022
DOI: 10.3389/fgene.2022.934223
|View full text |Cite
|
Sign up to set email alerts
|

YT521-B homology domain family proteins as N6-methyladenosine readers in tumors

Abstract: N6-methyladenosine (m6A) is the most abundant internal chemical modification of eukaryotic mRNA and plays diverse roles in gene regulation. The m6A modification plays a significant role in numerous cancer types, including kidney, stomach, lung, bladder tumors, and melanoma, through varied mechanisms. As direct m6A readers, the YT521-B homology domain family proteins (YTHDFs) play a key role in tumor transcription, translation, protein synthesis, tumor stemness, epithelial–mesenchymal transition (EMT), immune e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
0
0
Order By: Relevance
“…The GSEA results further showed that a high level of YTHDF3 was enriched in gene sets associated with the suppression of invasion and metastasis (Figure 2B,C), suggesting YTHDF3 correlated with the inhibition of ccRCC malignancy. Given that YTHDFs regulated tumor immunity and influenced tumor malignancy, 13,23,24 we also explored the relationship between YTHDF3 and tumor immune dysfunction.…”
Section: Ythdf3 Overexpression Suppresses Ccrcc Development and Immun...mentioning
confidence: 99%
“…The GSEA results further showed that a high level of YTHDF3 was enriched in gene sets associated with the suppression of invasion and metastasis (Figure 2B,C), suggesting YTHDF3 correlated with the inhibition of ccRCC malignancy. Given that YTHDFs regulated tumor immunity and influenced tumor malignancy, 13,23,24 we also explored the relationship between YTHDF3 and tumor immune dysfunction.…”
Section: Ythdf3 Overexpression Suppresses Ccrcc Development and Immun...mentioning
confidence: 99%